Stocking rate and supplementation for steers grazing intensively on early-stocked bluestem pasture - Held, R.; Smith, E.F.; Riley, Jack G.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
Native bluestem pastures were grazed by 520-lb steers from April 30 to July 14 at stocking rates of 1.7, 1.3 and 1.1 acres per steer. Daily gain of the steers was about the same for the two heavier stocking rates, but was slightly lower for the lightest rate (1.7 acres/steer). The gain per acre increased with each increase in stocking rate. Half of the steers were self-fed a salt-limited sorghum grain-rumensin mixture. Each steer consuming approximately 1.5 pounds per day of this mixture gained about a half a pound more per day (P<.05) than did each steer not fed the supplement (1.77 vs 1.27 lbs.). Gain per acre was increased by 33 lbs. with the supplementation.
Keywords: Beef; Stocking rate; Steers; Bluestem pasture